Peningkatan Kualitas Konten Multimedia Era Industri Digital - Andreas Tigor Oktaga; Ika Susanti (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
Multimedia content has now become an integral element in the digital industry which continues to grow rapidly. Due to technological advances and the widespread spread of the internet, the way people interact with digital content, such as video, audio, images, and all of them combined, has undergone significant changes. Multimedia content plays a key role in influencing consumer behavior, building brands and creating engaging user experiences. Although technological advances have enabled the production of better quality multimedia content, competitive challenges remain. Content producers need to continue to innovate to produce works that are unique and interesting to their audience and stay abreast of the latest technological developments. In addition to fierce competition, there are various other problems that can hinder the positive impact of multimedia content, such as fragmented information, improper dissemination of content, difficulties in attracting audience attention, and lack of creativity in content development. Therefore, in this digital industry era, multimedia content producers must also consider the needs and preferences of an increasingly diverse audience.